2013
DOI: 10.1515/cllt-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

Formulaicity in an agglutinating language: the case of Turkish

Abstract: This study examines the extent to which complex inflectional patterns found in Turkish, a language with a rich agglutinating morphology, can be described as formulaic. It is found that many prototypically formulaic phenomena previously attested at the multi-word level in English -frequent co-occurrence of specific elements, fixed 'bundles' of elements, and associations between lexis and grammar -also play an important role at the morphological level in Turkish. It is argued that current psycholinguistic models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…However, they did not analyze the learners' performances based on their first languages, and this handicap might have caused some fluctuations in the results as some learners could have been advantageous in terms of their first language. Considering the fact that the reading test scores of Turkish EFL learners are significantly under the average in TOEFL and IELTS (Educational Testing Service, 2012;IELTS, 2011), and given that there is an etymological distance between the two languages (i.e., Turkish is an Altaic language with an agglutinative morphology (Durrant, 2013) and English is an Indo-European language) it is of importance to scrutinize the relationship between vocabulary size and reading comprehension with Turkish students of English, as well. Since the participants shared the same L1 in this study, various L1s in this case did not have a fluctuating effect on the interpretation of the results.…”
Section: A Reciprocal Process: Reading Comprehension and Vocabulary Sizementioning
confidence: 99%
“…However, they did not analyze the learners' performances based on their first languages, and this handicap might have caused some fluctuations in the results as some learners could have been advantageous in terms of their first language. Considering the fact that the reading test scores of Turkish EFL learners are significantly under the average in TOEFL and IELTS (Educational Testing Service, 2012;IELTS, 2011), and given that there is an etymological distance between the two languages (i.e., Turkish is an Altaic language with an agglutinative morphology (Durrant, 2013) and English is an Indo-European language) it is of importance to scrutinize the relationship between vocabulary size and reading comprehension with Turkish students of English, as well. Since the participants shared the same L1 in this study, various L1s in this case did not have a fluctuating effect on the interpretation of the results.…”
Section: A Reciprocal Process: Reading Comprehension and Vocabulary Sizementioning
confidence: 99%
“…In addition to these typological aspects that affect the expression of motion, it is important to mention some general complexities of Turkish morphology. As documented by Durrant (2013), morphemic co-occurrences are much stronger in Turkish than lexical ones, which makes this a distinctive feature of constructional patterns in Turkish. In addition, English prepositions are known to pose difficulties for even advanced learners independent of the L1 background.…”
Section: Properties Of Verb Constructions In Turkishmentioning
confidence: 91%
“…English as a Lingua Franca (ELF) research has documented non-conventional uses of prepositions in contexts where English is used for oral communication by speakers of different L1s (Cogo & Dewey, 2010;Seidlhofer, 2004). Due to the combined influence of complex morphology in general (Durrant, 2013) and of expressing motion in particular (Jensen, 2014;Özyürek & Çalışkan, 2000), Turkish learners could have particularly marked challenges. For example, Çabuk (2009) and Özışık's (2014) analyses of the use of prepositions in Turkish learner English showed that Turkish learners tend to rely on L1 transfer, thus using prepositions that are similar to their L1, however mostly erroneously, such as marry with someone instead of marry someone.…”
Section: Properties Of Verb Constructions In Turkishmentioning
confidence: 99%
“…Bantu languages have a characteristically agglutinating morphology, which makes their structure rich and complex. The agglutinating typology is not unique to Bantu languages as other agglutinating languages with extremely complex morphology include Turkish, Hungarian, and Finnish [7]. In characterising the complexity of the verbal constructions in Bantu languages, [28] (p291) states that the morphology of the verb shows "[...] the fullest extent of the agglutinative nature of the Bantu language family".…”
Section: Basics Of the Isizulu Verbmentioning
confidence: 99%